PENGEMBANGAN MODUL MATEMATIKA BERBASIS LKS DENGAN PENDEKATAN PROBLEM BASED LEARNING - Zuhro, Anna Ulfatu (Study Program of Mathematics Education University of Muhammadiyah Malang, 2017)
This research was conducted to develop teaching materials modul-based mathworksheets (LKS) with problem based learning approach. By developing the teaching materials is expected to help students learn independently and improve students? ability in solving mathematical problems. The teaching materials developed with 4-D Thiagarajan development model that has been modified into 3-D that define, design, development. Validated teaching materials developed by lecturers and teacher of mathematics. The result were obtained validity for two aspects : the average material 4 and the average media aspect 4. These teaching materials declared valid. For the feasibility study gained an average of 4.1 and student response gained an average of 4.2, which was developed into simpleteaching materials. And as many as 26 students scored above the KKM with a percentage of 87% proved the effectivity of the teaching materials.